Optimal strategies for ecosystem services provision in Amazonian production forests. (20th December 2019) - Piponiot, Camille; Rutishauser, Ervan; Derroire, Géraldine; Putz, Francis E; Sist, Plinio; West, Thales A P; Descroix, Laurent; Guedes, Marcelino Carneiro; Coronado, Eurídice N Honorio; Kanashiro, Milton; Mazzei, Lucas; d'Oliveira, Marcus Vinicio Neves; et al.
Abstract: Although tropical forests harbour most of the terrestrial carbon and biological diversity on Earth they continue to be deforested or degraded at high rates. In Amazonia, the largest tropical forest on Earth, a sixth of the remaining natural forests is formally dedicated to timber extraction through selective logging. Reconciling timber extraction with the provision of other ecosystem services (ES) remains a major challenge for forest managers and policy-makers. This study applies a spatial optimisation of logging in Amazonian production forests to analyse potential trade-offs between timber extraction and recovery, carbon storage, and biodiversity conservation. Current logging regulations with unique cutting cycles result in sub-optimal ES-use efficiency. Long-term timber provision would require the adoption of a land-sharing strategy that involves extensive low-intensity logging, although high transport and road-building costs might make this approach economically unattractive. By contrast, retention of carbon and biodiversity would be enhanced by a land-sparing strategy restricting high-intensive logging to designated areas such as the outer fringes of the region. Depending on management goals and societal demands, either choice will substantially influence the future of Amazonian forests. Overall, our results highlight the need for revaluation of current logging regulations and regional cooperation among Amazonian countries to enhance coherent and trans-boundary forest management.